Effect of consumption of vegetables and fruit on nitric oxide levels and T-glutathione levels in type 2 diabetes mellitus patients - Prita Anggraini Kartika Sari; Endang Darmawan; Akrom Akrom (Universitas Ahmad Dahlan, 2022)
Glutathione is an antioxidant that plays a role in preventing free radicals and reducing oxidative stress, including in patients with type 2 diabetes mellitus (DMT2). One of the factors that affect glutathione status is the individual's ability to produce glutathione and in diabetic patients, T-glutathione levels have decreased. This study aims to determine the effect of fruit and vegetable consumption habits on plasma levels of T-Glutathione. This research method is analytic observational with cross sectional findings, the sample used is 85 subjects in the form of archives of biological materials. Data on habits of consuming vegetables and fruits were collected through interviews, plasma T-GSH levels were determined biochemically using the Elabscience GSH Assay Kit and then analyzed using the Mann Whitney test. The results showed that the average plasma T-GSH levels in patients with the habit of consuming vegetables and fruit and those who did not, were 13.54 Â± 3.34 mol/L and 12.73 Â± 1.44 mol/L, respectively, but not found a significant difference relationship (p = 0.222). This study provides information that the habit of consuming vegetables and fruit does not provide a significant difference to plasma T-GSH levels in T2DM patients. But these habits still need to be done for health maintenance. Further research is needed that is more specific to the amount and type of certain vegetables and fruits consumed and how to cook them.